Pantangan dan Larangan dalam Kehidupan Masyrakat Kajang: Analisis Etnografi terhadap Nilai Budaya - Sarna Pasawin (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2025)
This study investigates the system of customary taboos and prohibitions within the Kajang indigenous community in South Sulawesi, exploring its function in maintaining social order and cultural identity amid modernization. Employing a descriptive qualitative approach grounded in ethnographic methods, data were collected through participant observation, in-depth interviews, and document analysis conducted in Tana Toa, the cultural heart of Kajang. The findings reveal that customary restrictions extend beyond normative control; they embody core philosophical values such as simplicity (kamase-mase), egalitarianism, and ecological harmony. These taboos function as effective social instruments for conflict prevention, environmental conservation, and the reinforcement of communal solidarity, supported by traditional sanctions and multigenerational value transmission. The central role of the Ammatoa—a spiritual and customary authority—in interpreting and preserving Pasang ri Kajang (ancestral teachings) is vital to the continuity of this indigenous regulatory system. This study demonstrates that local wisdom, expressed through the taboo system, offers a resilient and adaptive framework for sustaining cultural identity and social cohesion. Furthermore, the findings provide an alternative perspective for developing culturally grounded policies in environmental conservation and indigenous community empowerment.